DEVELOPMENT OF THE PRODUCTION TECHNOLOGY OF ROLLED METAL ROUND WITH DIAMETER 17 MM IN STICKS OF SPRING STEEL OF TYPE 40C2 FOR PRODUCTION OF RAILWAY ELASTIC TERMINALS BRACING IN CONDITIONS OF RUP “BMZ” - O. M. Kirilenko; M. I. Titov; A. V. Rusalenko (Литьë и металлургия, 2006)
The technology of production of hot-rolled metal with diameter 17 mm in sticks of spring steel of type 40C2 for production of railway fasteners of elastic binding posts in conditions of RUP “BMZ” is given.